Manuel des Droits de l'Homme à l'Eau Potable et à l'Assainissement à l’intention des Praticiens (2018)
"Manuel des Droits de l'Homme et à l'Eau Potable et à l'Assainissement à l’intention des Praticiens is the French translation of Manual on the Human Rights to Safe Drinking Water and Sanitation for Practitioners. The Manual highlights the human rights principles and criteria in relation to drinking water and sanitation. It explains the international legal obligations in terms of operational policies and practice that will support the progressive realisation of universal access. The Manual introduces a human rights perspective that will add value to informed decision making in the daily routine of operators, managers and regulators. It also encourages its readership to engage actively in national dialogues where the human rights to safe drinking water and sanitation are translated into national and local policies, laws and regulations. Creating such an enabling environment is, in fact, only the first step in the process towards progressive realisation. Allocation of roles and responsibilities is the next step, in an updated institutional and operational set up that helps apply a human rights lens to the process of reviewing and revising the essential functions of operators, service providers and regulators. Contents Introduction; Main operational principles; Setting the scene – context and contents of the human rights to safe drinking water and sanitation; Translating the human rights to safe drinking water and sanitation into operational terms; Creating the enabling environment; . Incorporating HRWS into the essential functions of service providers; Addressing sensitive practices, dealing with challenges and avoiding pitfalls."